Implant placement in the removable mandibular advancement device for completely edentulous patients: a finite element study. Issue 1 (28th September 2020) - Park, Jieun; Ahn, Su-Jin; Lee, Hyeonjong; Noh, Gunwoo
Abstract: Few studies have examined the biomechanical effects of dental implant placement in the implant-supported mandibular advancement device (MAD) for the treatment of obstructive sleep apnea in completely edentulous patients. This biomechanical study aimed to evaluate the stability of the implant-supported MAD for different numbers and positions of dental implants. A 3D edentulous maxillofacial model with the one-piece MAD was considered for various numbers and positions of implants. On each mandible and maxilla, one, two, four, or six implants were placed symmetrically in various positions. Total 42 implant placements were considered. A static finite element analysis was performed under the mandibular posterior restorative force for 40% protrusion. The maximum and minimum principal stresses on the cortical and cancellous bones and the von Mises stresses on the implant were measured. When four implants were placed on each maxilla and mandible, the maximum average stress on the cancellous bone was reduced by up to approximately three times compared with the cases of placing two implants on each maxilla and mandible. The placement of at least four implants on each maxilla and mandible improved MAD stability. It is noteworthy that the mandibular implants should be arranged adjacently to avoid stress concentration in the second molar. Graphical Abstract: